Utilizing Breadfruit (Artocarpus altilis) Starch-Derived Maltodextrin as a Pharmaceutical Binder: Preparation and Evaluation in Paracetamol Formulations - Diki Zaelani; Ari Wibowo; Rahmat Santoso (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
This study aimed to explore the potential of breadfruit (Artocarpus altilis) starch as a renewable source for pharmaceutical-grade maltodextrin through enzymatic modification. The modified starch produced maltodextrin with a dextrose equivalent (DE) value of 4.30, placing it within the low-DE range suitable for use as a binder in tablet formulations. The maltodextrin was then applied as a binding agent in the production of paracetamol tablets using the wet granulation method. The resulting tablets were evaluated for key quality parameters including organoleptic properties, weight uniformity, size uniformity, hardness, friability, and disintegration time. The findings showed that tablets formulated with maltodextrin at concentrations of 5%, 7%, 9%, and 11% successfully met all pharmacopeial quality requirements. These tablets exhibited smooth and uniform appearance, acceptable hardness and friability, and disintegration times appropriate for immediate-release dosage forms. Statistical analysis using one-way ANOVA demonstrated significant differences among formulations for weight uniformity, size uniformity, and hardness (p < 0.05), indicating that varying maltodextrin concentrations had a measurable effect on tablet performance. Despite these differences, all acceptable formulations remained within the required limits. Overall, the study confirms that enzymatically modified breadfruit starch can be transformed into maltodextrin suitable for use as an effective binder in paracetamol tablet production. Optimal binder performance was achieved at concentrations between 5% and 11%. These findings highlight the potential of breadfruit as a locally sourced, sustainable raw material for pharmaceutical excipients, contributing to the development of alternative natural binders in tablet manufacturing.